PERAN PEMERINTAH KABUPATEN KOLAKA DALAM PENGUATAN EKONOMI MASYARAKAT PESISIR DI SEKTOR PERIKANAN - Firdani, Winda Sari; Mokodompit, Eliyanti Agus (Jurnal Multidisipliner Bharasumba, 2025)
This study aims to analyze the role of the Kolaka Regency Government in strengthening the coastal community's economy in the fisheries sector, identify effective policies, and provide strategic recommendations. The research method employs a descriptive quantitative approach with secondary data analysis from BPS, the Department of Marine and Fisheries, and policy documents. The results indicate that the fisheries sector in Kolaka significantly contributes to the regional GDP with stable growth, supported by infrastructure such as cold storage and Integrated Fish Processing Centers. However, challenges such as climate change, low fisher productivity, and limited market access hinder sectoral development. Policy recommendations include technological development, human resource capacity building, and multi-stakeholder collaboration to enhance the sustainable welfare of coastal communities.